N′-[(E)-4-Benzyloxy-2-hydroxybenzylidene]-4-nitrobenzohydrazide monohydrate - Joseph, Bibitha (International Union of Crystallography, 2012)
The title compound, C(21)H(17)N(3)O(5)·H(2)O, exists in the keto form with an E conformation with respect to the azomethine double bond. The twist angles between the aromatic rings are in the range 4.67 (10)–17.54 (10)°. A water molecule of solvation is present in the lattice. A conventional intramolecular O—H⋯N hydrogen bond increases the rigidity of the molecule. Intermolecular O—H⋯O, N—H⋯O and C—H⋯O hydrogen-bonding interactions establish a supramolecular linkage among the molecules in the crystal structure. There are also C—H⋯π interactions present.